GmCYP86A37 is a bifunctional cytochrome P450 essential for soybean root aliphatic suberin biosynthesis - Yeung, Lorena S.; Ong, Andrea; Dhaubhadel, Sangeeta; Bernards, Mark A. (Frontiers in Plant Science, 2026)
18-Hydroxyoleic acid and its dioic acid derivative, oleic-1,18-dioic acid, are the two most prominent aliphatic monomers in soybean root suberin. While hydroxylated fatty acids are known to be formed by cytochrome P450 monooxygenases (P450), mainly from the CYP86A and CYP86B subfamilies, the biosynthetic origin of their corresponding dioic acids in soybean remains unclear. Two root-expressed soybean P450 genes, GmCYP86A37 and GmCYP86B9 were cloned and expressed as recombinant enzymes in yeast. A third root-expressed soybean P450 gene (GmCYP86A38) was also cloned, but no recombinant protein was produced. In vitro assays demonstrated that GmCYP86A37 and GmCYP86B9 exhibited preference for the ω-hydroxylation of oleic acid (C18:1) and lignoceric (C24:0) acids, respectively. Surprisingly, in vitro production of oleic-1,18-dioic acid was also detected when GmCYP86A37 was supplied with oleic acid substrate. Furthermore, CRISPR/Cas9-mediated double knockout of Gmcyp86a37/38 resulted in substantial reduction of ω-hydroxylated fatty acids and dioic acids. These findings underscore the role of the CYP86A subfamily in soybean aliphatic suberin biosynthesis and provide direct evidence for GmCYP86A37 in the formation of oleic-1,18-dioic acid.